A conception on the terahertz communication system for plasma sheath penetration. Issue 13 (4th April 2012) - Li, Jin; Pi, Yiming; Yang, Xiaobo
ABSTRACT The signal of a hypersonic spacecraft entering the Earth's atmosphere may be lost at a certain altitude transitorily. This phenomenon is called "blackout, " an important performance feature of aircraft design. Recently, with the development of the nearcraft, communication techniques under the plasma environment have increasingly become more important, with the realization that we can record, monitor, track, and capture the nearcraft. In this paper, an idea based on the capability of radiation from the terahertz communication system to penetrate the plasma sheath is proposed to provide the theoretical basis for real‐time communication with the nearcraft. Copyright © 2012 John Wiley & Sons, Ltd.